2001
DOI: 10.1074/jbc.m011053200
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Steps of Phosphorylation Affect Conformation and DNA Binding of the Chironomus High Mobility Group A Protein

Abstract: The high mobility group (HMG) proteins of the AT-hook family (HMGA) lie downstream in regulatory networks with protein kinase C, Cdc2 kinase, MAP kinase, and casein kinase 2 (CK2) as final effectors. In the cells of the midge Chironomus, almost all of the HMGA protein (cHMGA) is phosphorylated by CK2 at two adjacent sites. 40% of the protein population is additionally modified by MAP kinase. Using spectroscopic and protein footprinting techniques, we analyzed how individual and consecutive steps of phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 53 publications
1
24
1
Order By: Relevance
“…Indeed, the ability to tweak both protein stability and conformation of the intrinsically unstructured HMGA proteins by covalent modifications such as phosphorylation or acetylation underlies their participation in diverse biological processes from transcription to recombination (18,62). The C-terminal HMGA-like part of CarD would be similarly malleable to such conformational and so functional alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the ability to tweak both protein stability and conformation of the intrinsically unstructured HMGA proteins by covalent modifications such as phosphorylation or acetylation underlies their participation in diverse biological processes from transcription to recombination (18,62). The C-terminal HMGA-like part of CarD would be similarly malleable to such conformational and so functional alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Protein conformational changes and decreases in DNA binding affinity are also brought about by phosphorylation by a number of kinases including CKII, Cdc2 kinase, mitogen-activated protein kinase, and protein kinase C (14 -18). This provokes fluctuations in intracellular protein stability and in DNA binding, thereby fine-tuning their regulatory functions in vivo (16,18).…”
mentioning
confidence: 99%
“…Further research revealed that HMGA1 proteins were phosphorylated by several kinases such as cyclindependent kinase 1 (previously known as cdc2 kinase) [12,13], protein kinase C (PKC) [14], and protein kinase CK2 [15]. These phosphorylations attenuated the DNA binding affinities of mammalian HMGA1a [14,16,17] and HMGA1b [17,18].…”
mentioning
confidence: 99%
“…The AT hooks have random structure when free but adopt a defined conformation on binding specifically to the narrow minor groove of AT-rich sequences 4 to 8 bp in length and present in at least two appropriately spaced tracts (20,25,43). Kinases such as casein kinase II (CKII) and Cdc2 phosphorylate HMGA proteins and modulate DNA binding as well as protein stability (14,32,36,41,47,49,50). This occurs in a cell cycle-and differentiationdependent manner and fine-tunes HMGA activity in vivo.…”
mentioning
confidence: 99%